Increasing the performance of techniques of rowing on yalks with a roll-up system based on kinematic analysis and computer simulation - Sheichenko, T. A.; Ponomarev, G. N.; Sheichenko, D. R. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify, on the basis of kinematic analysis and modeling, the effectiveness of using the developed rowing technique on yawls with a rolling system in the training process.